Foreword - CRĂCIUN, Maria (Studia Universitatis Babeș-Bolyai Historia, 2021)
The current issue is a collection of some of the best articles presented at the 2018 and 2019 editions of the conference of the Graduate School “History, Civilization, Culture”. While the conference itself has been an annual event for a number of years, the most recent development is its transformation into an international conference which welcomes students in the field of history from other countries in the world. Bearing this in mind, the organizers have decided to publish some of the papers presented in English as a supplement to the Studia Universitatis Babeş-Bolyai. Historia. This explains the wide-ranging topics that compel readers to travel from ancient to the most recent history, while the interdisciplinarity of the graduate school accommodates neighboring fields such as art history, historiography and the history of ideas, ethnography, cultural studies and anthropology. The foreword to this endeavour needs to mention however briefly all the people who have contributed to its successful accomplishment. Thanks are thus due to all our colleagues who supervised these PhD students and to all those who acted as chairs of the various panels and helped select the papers that were to be published. We are particularly grateful to Ion Indolean who helped with the editing of the articles and to Marcela Sălăgean who made their publication possible.